2017
DOI: 10.3390/coatings8010001
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Isothermal Oxidation Behavior of Zr-Doped, Pt-Modified Aluminide Coating Prepared by a Hybrid Process

Abstract: Abstract:To take advantage of the synergistic effects of Pt and Zr, a kind of Zr-doped, Pt-modified aluminide coating has been prepared by a hybrid process, first electroplating a Pt layer and then co-depositing Zr and Al elements by an above-the-pack process. The microstructure and isothermal oxidation behavior of the coating has been studied, using a Pt-modified aluminide coating as a reference. Results showed that the Zr-doped, Pt-modified aluminide coating was primarily composed of β-(Ni,Pt)Al phase, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…When ions of two dopants segregate along grain boundaries in an oxide scale, their interaction with Al ions is stronger than for one dopant's ions, i.e., a synergistic effect is observed [21]. The performed experiments confirmed that Pt + Zr co-doped aluminide coatings have better oxidation resistance and adhesion and lower surface roughness than any single-doped ones [22]. Moreover Zr-rich oxide pegs improve phase stabilities in the coating and reduce oxide scale growth rate [23].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…When ions of two dopants segregate along grain boundaries in an oxide scale, their interaction with Al ions is stronger than for one dopant's ions, i.e., a synergistic effect is observed [21]. The performed experiments confirmed that Pt + Zr co-doped aluminide coatings have better oxidation resistance and adhesion and lower surface roughness than any single-doped ones [22]. Moreover Zr-rich oxide pegs improve phase stabilities in the coating and reduce oxide scale growth rate [23].…”
Section: Introductionmentioning
confidence: 62%
“…The density of inclusions in the interdiffusion zone is much higher than in the additive zone (Figure 3), which results in a much finer microstructure (Figure 7). Even as the inclusions in the additive zone are fewer than those in the interdiffusion one, and therefore less effective in restricting grain growth, they diminish the formation of voids on the surface [22].…”
Section: Palladium and Zirconium Co-doped Aluminide Coatingmentioning
confidence: 99%
“…As Y and Zr atoms could encourage the formation of the stable α-Al 2 O 3 phase and reduce internal stress in the oxide scale as shown in Figure 9, it can be deduced that adding Zr and Y to the Cr-Co modified aluminide coating might increase the oxidation-resistance [19]. Numerous studies reveal that the effects of Y 2 O 3 are generally accepted to be as follows [23,24]: (1) to promote the selective oxidation of chromium by lowering the critical content for the formation of a continuous chromium scale, and (2) to slow down scaling by switching the scaling mechanism from dominant outward chromium diffusion in the absence of RE to dominant inward oxygen diffusion [24].…”
Section: Oxidation Behaviormentioning
confidence: 99%
“…The coating deposition is caused by the vapors transport via a packed bed (Al2O3) and cross -reactivity on the surface of a substrate. The following are typical pack reactions for a NaClactivated pack [19]:…”
Section: Microstructure Of Zr-modified Aluminide Diffusion Coatingmentioning
confidence: 99%